Social media : an intersection for phenomenology and critical theory - Nur Amirah Rosman (Nanyang Technological University, 2020)
What does it mean to connect with people? This paper first explores the phenomenology intersubjective connections and community building facilitated by social networking websites. Then I will examine the limitations of such a method in terms of the social and economic structures that operate in the background of online interactions. These structures present issues which phenomenology was not able to address previously. Such issues include the commercializing and exploitation of corporate social networking sites. I highlight how connection and community on social media is driven by underlying power structures and commodification, which are additional but important considerations on top of our first-person experiences. Thus, to maximize the benefits of social networking sites, a perceptive user must consider both analyses in a moderate, midway approach. I synthesize the method of phenomenology and critical theory together in my analysis to show how phenomenological bracketing reveals rather than restricts an analysis of online sociality. Specifically, I explore intersubjective relations to supplement a critical analysis of privacy and surveillance and explain how certain economic features on social networking sites contribute to our online experiences. These examinations will fortify the idea that the complexity of social networking sites warrant an examination through simultaneously different interdisciplinary lenses.